Abbott v. Abbott. (2014) - Unknown
Abstract : 639 Treaties — Interpretation — Hague Convention on the Civil Aspects of International Child Abduction, 1980 — United States and Chile Contracting States to Convention — Congress implementing Convention provisions through International Child Abduction Remedies Act — Parent having ne exeat right under Chilean law — Whether constituting right of custody under Convention — Whether giving rise to return remedy — Text of Convention — Object and purpose of Convention — Views of United States Department of State — Case law of other Contracting States to Convention — Relevance — The law of the United States